8. THE CURRENT STATUS OF MANAGEMENT OF PATIENTS WITH MULTIDRUG-RESISTANT TUBERCULOSIS IN HANOI (Vietnam Journal of Community Medicine, 2024)
Background: As one of 27 countries with a high TB burden in the world, Vietnam is also facing many challenges from TB, especially drug-resistant TB. In addition to the detection, diagnosis and treatment of drug-resistant TB, the management of drug-resistant TB patients also faces many difficulties.Objectives: Describing the current status of management of patients with multidrug-resistant tuberculosis in Hanoi, peroid 2011-2014. Analysis of advantages and disadvantages in the management of multidrug-resistant tuberculosis patients in Hanoi, period 2011-2014 Methods: Cross-sectional survey. Quantitative combined qualitative research. Results and conclusion: 7.3% of patients with drug-resistant TB were new treatment, the remaining 92.7% of patients have been treated for TB. Nearly 50% of patients were managed and treated after 1 day of detection, the others were received after 2 days or more. 5.2% of patients were treated as inpatients at Hanoi Lung Hospital, the remaining 94.8% of patients were treated as outpatients at commune and district.
Keywords: Management, drug-resistant TB, advantages, disadvantages.